ANALISA FAKTOR YANG BERHUBUNGAN DENGAN KELELAHAN KERJA PADA PEKERJA BAGIAN PRODUKSI DI ALUMUNIUM MANUFACTURING KOTA BATAM - Malahayati Rusli Bintang; Sukma Sahreny; Isramilda; Fidyan Khotimatul Arbi; Doni (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2025)
ABSTRACT Background: : Work fatigue is a condition where the body runs out of energy due to the extension of the work done. Work fatigue increases work errors and decreases performance. Reduced performance equals reduced productivity at work. When the level of worker productivity is disrupted by physical and mental fatigue, the result is reduced company productivity. Methods: This research method is quantitative with an observational analytic research design with a cross sectional approach. The sample for this study were workers in the production section of PA (Casting) at Alumunium Manufacturing of Batam City totaling 40 people were selected based on inclusion and exclusion criteria. The analytical test used is the Chi-Square test and regresion logistic test. Results: Based on the results of the Chi-Square test on work intensity with work fatigue, it is known that there is a significant value of 0.001 (<0.05). Namely states that there is a significant influence between work intensity and work fatigue. Then on the circadian rhythm with work fatigue the p-value is 0.001 (<0.05), which states that there is a significant influence between circadian rhythm and work fatigue. And on psychological state and work fatigue the p-value is 0.001 (<0.05), which states that there is a significant influence between psychological state and work fatigue. Based on the results above, it can be concluded that the most influential factor is work intensity with a p-value (0.000) and a coefficients beta value (0.511). Conclusion: Based on the results of the study it can be concluded that Ho is rejected, which means that there is a significant influence between work intensity, circadian rhythm and psychological state on work fatigue in production workers at Alumunium Manufacturing Indonesia, Batam City. Based on the results of the multivariate test, the most influential is work intensity. Keywords: Work Intensity, Circadian Rhythm, Psychological State, and Work Fatigue